Persistent Peril: Confronting Recurrent Chest Abscess from Nontuberculous Mycobacteria - P Prem Ananth; R Anand; S Raghul Raj; N Nagarajan; M Thoupikka (Journal of Association of Pulmonologist of Tamil Nadu)
Recurrent chest wall abscesses, particularly those caused by nontuberculous mycobacteria (NTM) such as Mycobacterium fortuitum, are uncommon and pose significant diagnostic and therapeutic challenges. Our case report details a 42-year-old male with recurrent chest wall abscess, where the underlying etiology was traced to a near-drowning incident at the age of 18. Near-drowning incidents can lead to the aspiration of contaminated water, allowing waterborne pathogens, including NTM to enter the body and establish chronic infections. It also underscores the importance of considering environmental exposure in the pathogenesis of NTM infections and highlights the need for a multidisciplinary approach to effectively manage such complex cases.